2008
DOI: 10.4049/jimmunol.180.1.171
|View full text |Cite
|
Sign up to set email alerts
|

Loss of IL-7R and IL-15R Expression Is Associated with Disappearance of Memory T Cells in Respiratory Tract following Influenza Infection

Abstract: Following influenza virus infection, memory CD8 T cells are found in both lymphoid and nonlymphoid organs, where they exhibit striking differences in survival. We have assessed persistence, phenotype, and function of memory CD8 T cells expressing the same TCR in the airways, lung parenchyma, and spleen following influenza virus infection in mice. In contrast to memory CD8 T cells in the spleen, those residing in the airways gradually lost expression of IL-7R and IL-15R, did not respond to IL-7 and/or IL-15, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 34 publications
4
39
0
Order By: Relevance
“…tail injection of 10,000 CFUs of wild-type LM 10403S into B6 mice will yield millions of CFUs in both the spleen and liver 3 d postinfection, whereas the bacterial load following the same dose of rLM-SIY will border the limit of detection (data not shown). Notably, a recent study has demonstrated that 2C T cells can differentiate into longlived memory T cells, persisting at least 225 d postinfection, using a recombinant influenza virus expressing the SIY peptide, named WSN-SIY (48). By contrast to rLM-SIY infection, Ag is detectable for at least 8 d postinfection after WSN-SIY infection (J. Chen, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…tail injection of 10,000 CFUs of wild-type LM 10403S into B6 mice will yield millions of CFUs in both the spleen and liver 3 d postinfection, whereas the bacterial load following the same dose of rLM-SIY will border the limit of detection (data not shown). Notably, a recent study has demonstrated that 2C T cells can differentiate into longlived memory T cells, persisting at least 225 d postinfection, using a recombinant influenza virus expressing the SIY peptide, named WSN-SIY (48). By contrast to rLM-SIY infection, Ag is detectable for at least 8 d postinfection after WSN-SIY infection (J. Chen, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, IL-7 participates in T-cell responses to antigenic stimulation. [35][36][37] Moreover, most of the molecules that were induced after IL-7 treatment were described as participating in T-cell homing into these organs during inflammatory reactions. [38][39][40][41][42] The expression patterns of chemokines/chemokine receptors suggest that naive and memory CD4 ϩ T cells are directed to the gut through CCR6/CCL20 and/or CCR9/CCL25 expression, whereas all T-cell subsets (but the TEM CD8 ϩ , which barely express CCR7) might migrate into the skin and the lungs where CCR7-ligands (CCL19, CCL21) expression is increased.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant WSN-SIY virus encoding the SIY epitope in the neuroaminidase stalk was described previously (29). Mice were anesthetized with 2,2,2-tribromoethanol (Avertin) and infected either i.n.…”
Section: Methodsmentioning
confidence: 99%